Study of loose bulk cargo storage conditions and water transportation - Novikova Tatyana (EDP Sciences, 2021)
When transporting such cargos as mineral fertilizers by water, they absorb moisture, which stimulates cargo self-heating and ultimately leads to dangerous temperature limits. When transporting ANP fertilizer in holds, its equilibrium moisture content can change significantly, which can lead to the cargo damage. The article presents the findings on the processes of hydrothermal moistening of porous bodies on the example of ANP fertilizer associated with the phenomena of sorption and desorption. There is no analytical description of moistening processes of porous bodies associated with these phenomena in the scientific literature. The optimal conditions for storage and transportation of bulk materials have been determined on the example of ANP fertilizer transported through the Novorossiysk seaport. As a result of the study, the moisture content intervals associated with various types of absorption were established. Thus, in the range of ⱷ from 0% to 16% moisture content, monomolecular adsorption prevails, which corresponds to the normal moisture content of ANP fertilizer. In the range of ⱷ from 16% to 54%, polymolecular adsorption predominates, and at the value of ⱷ greater than 87%, a smooth transition from predominantly polymolecular adsorption to capillary condensation occurs, which will negatively affect the process of humidification and cargo caking.